A comparative study between tinnitus masking and tinnitus retraining therapy on perceived tinnitus handicap and cognition - Chatterjee, Indranil; Gore, Geeta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Since last one decade there were no such studies done in India on the efficacy of tinnitus retraining therapy (TRT) on tinnitus treatment. Here, in this study we try to find out whether TRT is an effective tool than tinnitus masking as a treatment procedure of tinnitus in Indian context. Methods: A total of 60 participants (with no prior history of presence of hearing loss) were divided into two groups. Group 1 was consisted of 30 subjects provided tinnitus masking using relief app at the ease of their home environment for 2 months. Group 2 was consisted of another 30 subjects have been provided tinnitus retraining therapy (TRT) for 2months (60 sessions). The design is experimental design. The study was carried out in eight phases. Results: The findings of this study suggested that both the tinnitus masking therapy as well as TRT helped tinnitus sufferers to improve after 60 days of therapy continuation at initial stage. But a significant marked difference was found in terms of performance in participants from group 2 who had undergone TRT i.e., they performed very well after one month of post transfer therapeutic sessions than those who had undergone tinnitus masking therapy. Conclusions: The findings of this study are suggestive of that TRT is more effective than tinnitus masking therapy in tinnitus individuals even after one month of stopping therapy sessions. It also suggests that TRT has a long-term effect on tinnitus management than tinnitus masking.